Penerapan Teknik Pijat Oksitosin terhadap Peningkatan Produksi Asi pada Ibu Post Partum - Ina Shintia Oktapia; Endah Sari Purbaningsih; Erida Fadila (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Delayed onset of breast milk production is a common problem experienced by postpartum mothers and can lead to failure to achieve exclusive breastfeeding. This condition may be influenced by insufficient stimulation of the hormone oxytocin, maternal anxiety, and a lack of knowledge regarding proper breastfeeding techniques. The purpose of this study was to analyze the application of oxytocin massage on breast milk let-down in postpartum mothers with ineffective breastfeeding nursing problems. This study used a case study design with a nursing care approach on five postpartum mothers experiencing delayed breast milk let-down in the Mawar Ward of Kardinah Regional General Hospital, Tegal City. Data collection was conducted through interviews, observations, physical examinations, and document reviews. The nursing interventions provided included breastfeeding education, family support, and oxytocin massage for 10–15 minutes over three consecutive days. The study results showed that all patients experienced improved milk let-down, characterized by smoother milk flow, increased breastfeeding frequency, babies appearing calmer after feeding, and improved maternal proficiency in performing proper breastfeeding techniques. Additionally, mothers’ knowledge regarding exclusive breastfeeding and oxytocin massage also increased. The application of oxytocin massage has been proven to help increase milk production in postpartum mothers and can therefore be used as an evidence-based nursing intervention to support the success of exclusive breastfeeding.